Dificuldades na edição de manuscritos latinos medievais de lição única - Rebelo, António Manuel Ribeiro (2011)
The author discusses several opinions on the critical edition of medieval latin texts, trying to find a satisfactory way of handling the multiplicity of theories and procedures applicable to textual criticism of medieval latin texts, especially those preserved in only one manuscript.